Islamic Values, Governance, and Poverty Alleviation: Empirical Evidence from the Perspective of Middle Eastern and North African Countries - Risangaji, Syafiqri Aestro; Darwanto (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This study analyzes the relationship between the Islamic Human Development Index (I-HDI), Zakat, and institutional quality in addressing poverty in the Middle East and North Africa (MENA) region. Using panel data, researchers measured the relationship of these three instruments to poverty in Algeria, Lebanon, Morocco, Egypt, and Jordan from 2011 to 2022. The results indicate that increases in I-HDI scores and institutional quality, represented by variables such as voice and accountability, regulatory quality, and control of corruption, have a significant negative impact on the poverty level. Surprisingly, Zakat was found to be insignificant. This suggests that although Zakat plays an important role in wealth redistribution and meeting the needs of vulnerable communities, challenges such as administrative inefficiencies and economic and political instability in the MENA region can diminish its impact on poverty alleviation. These findings provide important insights for policymakers in efforts to reduce poverty and promote inclusive development in the MENA region, highlighting the need for a holistic approach that considers various factors to achieve optimal results.